Antihyperalgesic and antidepressive actions of (R)-(+)-limonene, α-phellandrene, and essential oil from Schinus terebinthifolius fruits in a neuropathic pain model. (July 2015) - Piccinelli, Ana Claudia; Santos, Joyce Alencar; Konkiewitz, Elisabete Castelon; Oesterreich, Silvia Aparecida; Formagio, Anelise Samara Nazari; Croda, Julio; Ziff, Edward Benjamim; Kassuya, Cândida Aparecida Leite
Abstract : Objectives: Previous studies have shown that essential oil containing (R)-(+)-limonene and α-phellandrene, extracted from fruits of Schinus terebinthifolius Raddi, exhibit anti-inflammatory activity. This work aimed to verify the antihyperalgesic and antidepressive actions of (R)-(+)-limonene, α-phellandrene, and essential oil from S. terebinthifolius fruits in spared nerve injury (SNI) model of neuropathic pain in rats. Methods: In the present work, essential oil from fruits of S. terebinthifolius, as well as the pure (R)-(+)-limonene and α-phellandrene compounds, were assayed for their effects on SNI-induced mechanical and cold hyperalgesia, and depressive-like behavior (immobility in forced swim test) in rats. The locomotor activity was evaluated in open-field test. Results: Oral administration for up to 15 days of essential oil of S. terebinthifolius (100 mg/kg), (R)-(+)-limonene (10 mg/kg), α-phellandrene (10 mg/kg), and also subcutaneous 10 mg/kg dose of ketamine (positive control) significantly inhibited SNI-induced mechanical hyperalgesia and increased immobility in the forced swim test. On the 15th day of oral treatment, α-phellandrene, but neither the essential oil from S. terebinthifolius nor (R)-(+)-limonene, prevented the SNI-induced increase in sensitivity to a cold stimulus. The oral treatment with essential oil (100 mg/kg) or with compounds (10 mg/kg) did not interfere on locomotor activity. Discussion: Together, the results of the present work show that essential oil of S. terebinthifolius and compounds present in this oil, including (R)-(+)-limonene and α-phellandrene, exhibit antihyperalgesic effects against mechanical hyperalgesia, and are antidepressive, while only α-phellandrene inhibited cold hyperalgesia in SNI rats.